Pre‐ and postoperative magnetic resonance imaging (MRI) findings in patients treated with laparoscopic sacrocolpopexy. Is it a safe procedure for all patients?. Issue 1 (8th May 2017) - Zacharakis, Dimitrios; Grigoriadis, Themos; Bourgioti, Charis; Pitsouni, Eleni; Protopapas, Athanasios; Moulopoulos, Lia A.; Athanasiou, Stavros
Abstract : Introduction: Laparoscopic sacrocolpopexy (LSCP) is a reference operation for apical compartment prolapse repair. Aim of this study is to describe the early and midterm postoperative MRI findings of the lumbosacral region (LSR) in patients undergoing LSCP and to detect any imaging changes that the presence of the mesh may cause on patients with preexisting degenerative disease of the LSR. Methods: Patients with POP‐Q grade III and IV uterovaginal or vaginal vault prolapse who were considered eligible for LSCP were invited to participate. An MRI of the LSR was performed preoperatively and then 3 and 12 months postoperatively. Patients with vaginal vault prolapse underwent LSCP, while women with uterovaginal prolapse were treated with the vaginally assisted laparoscopic sacrocolpopexy (VALS). Results: A total of 30 patients were included in the study; 18 (60%) underwent LSCP and 12 (40%) VALS. On preoperative MRIs, 83.3% (25/30) of patients had degenerative changes and 70% (21/30) reported having low back pain (LBP). Postoperative MRIs did not reveal any imaging changes compared to the preoperative MRI findings both for patients with or without preexisting degenerative abnormalities of the LSR. No significant changes in the LBP score were observed postoperatively. Conclusions: Any bone marrow or soft‐tissue changes at MRIs of the LSR early after the insertion of a synthetic mesh, does not constitute an expected postoperative finding and should raise the suspicion of an ongoing inflammatory or infectious spinal process (spondylodiscitis). Additionally, LSCP seems to be a safe surgical approach for women with preexisting degenerative disease of the LSR.